A RARE CASE OF TOTAL LEFT ANTERIOR CIRCULATION INFARCT (TACI) SECONDARY TO THYROTROPINOMA (TSHoma) TREATED WITH OCTREOTIDE MEDICAL THERAPY - Chua, Yi Jiang; Sun, Choon Peng; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND TSHoma is a rare cause of functioning pituitary adenoma. Patients with TSHoma have a biochemical derangement of elevated free thyroid hormones with unsuppressed TSH. They are usually misdiagnosed and treated for primary hyperthyroidism at the initial diagnosis. Most common symptoms upon presentations are hyperthyroidism, goitre and visual field defects. We reported an asymptomatic middle-aged female who presented acutely with left TACI secondary to atrial fibrillation due to a large functioning TSHoma. CASE A 53-year-old female, with no known medical diseases, presented with sudden-onset aphasia and right-sided body weakness. She presented to the emergency department with hypertension and tachycardia and ECG showed fast atrial fibrillation. Thyroid function test (TFT) showed that patient had a discordant hyperthyroid result [FT4 51.1 pmol/L (reference range 7.9-14.4) and TSH 4.825 mU/L (reference range 0.34-5.60)]. Repeated TFT on another platform had similar results. MRI of the brain revealed a heterogeneous mass occupying the sellar region with suprasellar extension 1.8 x 2.6 x 3.7 cm (AP x W x CC). TRH stimulation testing confirmed a functioning TSHoma and the patient was started on IM Octreotide LAR with rapid improvement of the TFT and resolution of the atrial fibrillation within 2 months. As this patient was not fit for surgical operation during the acute presentation, she was treated with medical therapy of Octreoride LAR and the patient achieved good improvement in 6 months’ time where she was able to function independently. A repeat MRI after 6 months showed a smaller sellar mass (1.6 x 2.3 x 3.5 cm). CONCLUSION TSHoma with acute stroke as an initial manifestation is uncommon. Interpretation of discordant TFT needs to be done and investigated carefully as TSHoma can be cured by surgical removal. In inoperable cases, medical therapy can control the disease well.